IMPROVING FINANCIAL CONTROL MECHANISMS IN ENSURING REGIONAL ECONOMIC STABILITY - Tulkinova Laylo Anvar kizi (Ecominds Press, 2025)
This article analyzes the role and importance of financial control mechanisms in ensuring regional economic stability. The relevance of an effective financial control system in the context of globalization is highlighted in strengthening economic security, ensuring budget discipline, rational use of financial resources, and reducing corruption risks. In the process of researching the topic, a systematic approach, comparative analysis, expert assessment, and economic modeling methods were used. The results of the study show that in order to improve financial control at the regional level, it is necessary to strengthen internal audit, introduce electronic financial control systems, increase transparency over public procurement, modernize taxation mechanisms, and strengthen public control. The article develops proposals and recommendations on strengthening financial discipline at the regional level based on advanced foreign experience. The results of the study serve as a practical basis for improving the effectiveness of economic reforms, ensuring sustainable economic development in the regions, and modernizing the state financial management system.
Keywords: Financial control, regional economy, economic stability, budget discipline, internal audit, electronic control system, state finance, fiscal policy, transparency, economic security.